Partnerships and networking in science and technology for development (UN New YorkUS, 2002)
Describes how the potential of partnerships can be harnessed to support technological prowess, economic competitiveness and national capacity building. Focuses on what it means to have a partnership and how to enter it, manage it and terminate it.
Keywords: PARTNERSHIP